Diagnosis of spondyloarthritis: should we need new criteria? - I. Z. Gaidukova; A. I. Akulova; A. V. Aparkina; A. P. Rebrov (Современная ревматология, 2015)
A large number of classification criteria for spondyloarthritis (SpA) are simultaneously used in modern rheumatology in the almost complete absence of diagnostic criteria. This poses a number of problems, among which there are two most important ones: 1) the frequent use of classification criteria to make a diagnosis in real clinical practice; 2) the possibility of stating different nosological entities of SpA in one patient in the presence of the same clinical picture.Objective: to investigate the specific features of the diagnosis of SpA and the use of its classification criteria in clinical practice.Subjects and methods. The investigation enrolled 119 patients with the established diagnosis of ankylosing spondylitis (AS), psoriatic arthritis (PsA), undifferentiated axial or peripheral SpA. Whether their clinical picture complied with the modified New York criteria, the European Spondyloarthropathy Study Group (ESSG) criteria, the Amor criteria, and the Assessment of Spondyloarthritis International Society (ASAS) classification criteria for axial and peripheral SpA and whether the Russian version of the modified New York criteria complied with the Classification criteria of Psoriatic ARthritis (CASPAR) were determined in the patients.Results. Sixty-three patients diagnosed with AS (M45), 44 with PsA (M07.0-07.3), 8 with undifferentiated SpA (M46.9), and 4 with nonradiographic axial SpA (M46.8) were followed up by attending physicians. The latter diagnosed AS in 10 patients who met the ASAS criteria for axial PsA but not the modified New York criteria. Twenty-one patients diagnosed as having PsA simultaneously met both the CASPAR criteria and the modified New York criteria, which could establish the diagnosis of AS in these cases. Eighty-one (68.0%) out of the 119 patients met the Amor criteria; 98 (82.3%) patients, the ESSG criteria; 91 (76.5%), the ASAS criteria for axial SpA; 18 (15.1%), the ASAS criteria for peripheral SpA; 76 (63.8%), the modified New York criteria; 88 (73.9%), the Russian version of the modified New York criteria; 42 (32.3%), the CASPAR criteria. No intersection of criteria was observed in only 5 patients; 113 (94.9%) patients met ≥2 criteria; 96 (80.7%), ≥3 criteria; 81 (68.1%), ≥4 criteria; 66 (55.5%), simultaneously ≥5 criteria; and 18 (15.1%), simultaneously 6 criteria.Conclusion. Most patients with SpA meet ≥2 classification criteria, which gives the chance to state ≥2 nosological entities in the same patient. This demonstrates the elaboration of diagnostic criteria that can make a clear distinction between different forms of SpA in clinical practice.